Dose adjustment of follicle-stimulating hormone (FSH) during ovarian stimulation as part of medically-assisted reproduction in clinical studies: a systematic review covering 10 years (2007-2017) - Human Fatemi; Wilma Bilger; Deborah Denis; Georg Griesinger; Antonio La Marca; Salvatore Longobardi; Mary Mahony; Xiaoyan Yin; Thomas D'Hooghe (BMC, 2021)
Abstract Background Individualization of the follicle-stimulating hormone (FSH) starting dose is considered standard clinical practice during controlled ovarian stimulation (COS) in patients undergoing assisted reproductive technology (ART) treatment. Furthermore, the gonadotropin dose is regularly adjusted during COS to avoid hyper- or hypo-ovarian response, but limited data are currently available to characterize such adjustments. This review describes the frequency and direction (increase/decrease) of recombinant-human FSH (r-hFSH) dose adjustment reported in clinical trials. Methods We evaluated the proportion of patients undergoing ART treatment who received ≥ 1 r-hFSH dose adjustments. The inclusion criteria included studies (published Sept 2007 to Sept 2017) in women receiving ART treatment that allowed dose adjustment within the study protocol and that reported ≥ 1 dose adjustments of r-hFSH; studies not allowing/reporting dose adjustment were excluded. Data on study design, dose adjustment and patient characteristics were extracted. Point-incidence estimates were calculated per study and overall based on pooled number of cycles with dose adjustment across studies. The Clopper-Pearson method was used to calculate 95% confidence intervals (CI) for incidence where adjustment occurred in < 10% of patients; otherwise, a normal approximation method was used. Results Initially, 1409 publications were identified, of which 318 were excluded during initial screening and 1073 were excluded after full text review for not meeting the inclusion criteria. Eighteen studies (6630 cycles) reported dose adjustment: 5/18 studies (1359 cycles) reported data for an unspecified dose adjustment (direction not defined), in 10/18 studies (3952 cycles) dose increases were reported, and in 11/18 studies (5123 cycles) dose decreases were reported. The studies were performed in women with poor, normal and high response, with one study reporting in oocyte donors and one in obese women. The median day that dose adjustment was permitted was Day 6 after the start of treatment. The point estimates for incidence (95% CI) for unspecified dose adjustment, dose increases, and dose decreases were 45.3% (42.7, 48.0), 19.2% (18.0, 20.5), and 9.5% (8.7, 10.3), respectively. Conclusions This systematic review highlights that, in studies in which dose adjustment was allowed and reported, the estimated incidence of r-hFSH dose adjustments during ovarian stimulation was up to 45%.